Changes in carbohydrate concentration and amylolytic activity in germinating maize - Breen, C M (Rhodes University, Faculty of Science, Botany Department, 1969)
Changes in the concentration of some carbohydrates and in amylolytic activity have been followed during germination of Zea. Mays L. var. Hickory King and var. Early Pearl. Assay techniques have been developed which permitted assay of individual grains. Thus during the investigation both groups and individual grains were used as samples. The use of groups permitted control of assay technique. Length of radicle, coleoptile and lateral roots were recorded in order to permit quantitative estimation of correlation between growth and the concentration of the various carbohydrates. Initially, during the study of changes in the carbohydrate concentration in Hickory King grains, total reducing sugar, sucrose and dextrin concentrations were estimated. However, the results obtained for changes in dextrin concentration, although reproduceable, thereby indicating reliable assay technique, presented a confusing picture and, in view of the apparent importance of sucrose and reducing sugar concentration, assay of dextrin concentration was discontinued in a subsequent study of Early Pearl. Instead changes in total reducing sugar, sucrose and glucose concentrations were followed. The results revealed that there is very considerable variability in physiological activity between grains subjected to the same germination conditions. However, all, irrespective of variety, follow the same basic metabolic pattern during germination. The trends observed were: (i) Reducing sugar accumulates slowly during the first 72-96 hours germination, but thereafter accumulation is very rapid, although concentration may decrease towards the end of the gestation period. (ii) Glucose follows a similar pattern to reducing sugar, accumulating slowly during the early stages of germination, followed by a period of rapid increase in concentration, which may decrease towards the end of the germination period. (iii) Sucrose concentration in dormant grains is fairly high, but it decreases markedly during the first 96 hours germination. This is followed by a phase of sucrose accumulation. (iv) Dextrin concentration shows two peaks. Initial level is low, but it accumulates rapidly during the first 72 hours. The level decreases between 72 and 120 hours but increases when the germination period is increased to 192 hours, after which there is a marked decrease. It was impossible, from the data relating to the study of individual grains, to discern a trend in dextrin concentration. With the exception of dextrin, about which there is little information, the results are in general agreement with the literature. Investigation of correlation between the various carbohydrates and between these and growth revealed that: (i) reducing sugar concentration and growth are positively correlated ; (ii) glucose concentration and growth are positively correlated; (iii) sucrose and reducing sugar concentrctions are negatively correlated during the initial stages of germination; (iv) sucrose and glucose concentrations are negatively correlated during early germination; (v) glucose and reducing sugar are positively correlated; (vi) in general, correlation between growth and concentration of the carbohydrates studied, decreases during the later periods of germination. These observations suggested that growth was, at least during the early stages of germination, dependent on the level of reducing sugar, and more particularly on the level of glucose, and that sucrose is the principal source of reducing sugar during this period. The relationship between amylase activity (total alpha- and beta-amylase activity) and reducing sugar concentration tends to be curvilinear, which suggests that amylolytic activity produces relatively little reducing sugar during early gennination, even though amylase activity and growth may be positively correlated. The results suggest, contrary to the observations of previous workers, that alpha-amylolytic activity may be present in dormant grains and that maize is not characterised by low levels of beta-amylase activity during germination. From the observations it is concluded that the initinl accumulati on of reducing sugar is the result of sucrose hydrolysis, and therefore sucrose is an importnnt metabolite durjng early germination. Amylolytic activity contributes little reducing sugar durlng the initia1 stages of germinatIon but that after approximately 72 hours it represents the major source of reducing sugar.
Keywords: Corn -- Research; Corn -- Analysis